Graded organ response and progression criteria for kidney immunoglobulin light chain amyloidosis - Muchtar, Eli; Wisniowski, Brendan; Geyer, Susan; Palladini, Giovanni; Milani, Paolo; Merlini, Giampaolo; Schönland, Stefan; Veelken, Kaya; Hegenbart, Ute; Leung, Nelson; Dispenzieri, Angela; Kumar, Shaji K.; et al. (JAMA oncology, 2024)
Kidney light chain (AL) amyloidosis is associated with a risk of progression to kidney replacement therapy (KRT) and death. Several studies have shown that a greater reduction in proteinuria following successful anticlonal therapy is associated with improved outcomes.To validate graded kidney response criteria and their association with kidney and overall survival (OS).This retrospective, multicenter cohort was conducted at 10 referral centers for amyloidosis from 2010 to 2015 and included patients with kidney AL amyloidosis that was evaluable for kidney response and who achieved at least hematologic partial response within 12 months of diagnosis. The median follow-up was 69 (54-88) months. Data analysis was conducted in 2023.Four kidney response categories based on the reduction in pretreatment 24-hour urine protein (24-hour UP) levels: complete response (kidCR, 24-hour UP ≤200 mg), very good partial response (kidVGPR, >60% reduction in 24-hour UP), partial response (kidPR, 31%-60% reduction), and no response (kidNR, ≤30% reduction). Kidney response was assessed at landmark points (6, 12, and 24 months) and best kidney response.Cumulative incidence of progression to KRT and OS.Seven-hundred and thirty-two patients (335 women [45.8%]) were included, with a median (IQR) age of 63 (55-69) years. The median (IQR) baseline 24-hour proteinuria and estimated glomerular filtration rate was 5.3 (2.8-8.5) g per 24 hours and 72 (48-92) mL/min/1.73m2, respectively. In a competing-risk analysis, the 5-year cumulative incidence rates of progression to KRT decreased with deeper kidney responses as early as 6 months from therapy initiation (11%, 12%, 2.1%, and 0% for kidNR, kidPR, kidVGPR, and kidCR, respectively; P = .002) and were maintained at 12 months and 24 months and best kidney response. Patients able to achieve kidCR/kidVGPR by 24 months and at best response had significantly better OS compared with kidPR/kidNR. Kidney progression, defined as a 25% or greater decrease in estimated glomerular filtration rate, was associated with cumulative incidence of progression to KRT and OS.The results of this cohort study suggest that graded kidney response criteria offers clinically and prognostically meaningful information for treating patients with kidney AL amyloidosis. The response criteria potentially inform kidney survival based on the depth of reduction in 24-hour proteinuria levels and demonstrate an OS advantage for those able to achieve kidCR/kidVGPR compared with kidPR/kidNR. Taken together, achievement of at least kidVGPR by 12 months is needed to ultimately improve kidney and patient survival.